"The Spiritual Man Discerns All Things": Watchman Nee, Theological Interpretation, and the Retrieval of a Classical Hermeneutic - Reardon, Michael M. C. (中国基督教研究（ISSN：3068-479X）, 2025)
Though not well-known within the Western academy, Watchman Nee (1903–1972) offers a robust, pneumatologically-governed hermeneutic that merits serious scholarly consideration within the burgeoning line of inquiry into the theological interpretation of Scripture (TIS). Positioned at the intersection of postliberal theology, patristic retrieval, and global Christianity, Nee’s interpretive methodology emerges as a sustained retrieval of pre-critical exegesis that is grounded in testamental unity and figural exegesis. The article begins by surveying the emergence of TIS in evangelical circles, the postliberal critique of historical criticism, and constructive proposals advanced by Hans Frei, George Lindbeck, Ephraim Radner, and others. Thereafter, I provide a brief overview of Nee’s life, both to highlight his key doctrinal commitments and to identify potentially formative influences upon his theological outlook. The essay then narrows focus to Nee’s hermeneutical methodology, which incorporates his trichotomistic anthropology, prioritization of the person of interpreters above exegetical methods, rejection of higher criticism, and governing principles related to figural and typological interpretations. Lastly, we engage in a close reading of The God of Abraham, Isaac, and Jacob. In this volume, Nee engages in an extended reflection upon the tripartite divine name utilizing typology and figural exegesis to articulate a model of trinitarian relations, an experiential theology of believers’ spiritual transformation, and a biblically grounded ecclesiological vision. The article concludes by arguing that Nee’s hermeneutic constitutes a vital, global expression of theological interpretation that should be integrated into the ongoing reconfiguration of biblical interpretation in the Western academy.